If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9 = x + 23 Reorder the terms: 9 + 8x = x + 23 Reorder the terms: 9 + 8x = 23 + x Solving 9 + 8x = 23 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 8x + -1x = 23 + x + -1x Combine like terms: 8x + -1x = 7x 9 + 7x = 23 + x + -1x Combine like terms: x + -1x = 0 9 + 7x = 23 + 0 9 + 7x = 23 Add '-9' to each side of the equation. 9 + -9 + 7x = 23 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 23 + -9 7x = 23 + -9 Combine like terms: 23 + -9 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 8sin^2x+4cos^2x=7 | | 3cosx+2sin^2x=0 | | 6(a+2)+10=16-a+27 | | 8c-9=7c+4 | | sin(0.5x)=-1.5 | | 2t+1=t+8 | | 2(a+1)=14+a | | R=60q+q^2 | | 3t+1=t+8 | | =60Q-Q^2 | | xsquare+37x+210=0 | | 14=2(a-2) | | iz^2-3z-2i=0 | | iz^2+3z-2i=0 | | 3t+3=t+8 | | 14+a=2(a-4) | | 10x^3-7x-3=0 | | kx^2-kx^2=-1 | | X+35=6x | | 4-7a+15-8a-21= | | 1.5x+4=0.25x-3 | | 16h^4-8h^2+1=0 | | 0.875t-2=0.375t+9 | | 2(4x-1)+3x=-13o | | 22.67647059= | | 6=4*-10 | | y=29 | | 5x-4=x+32 | | 5x^4+16x^3+12x^2=0 | | 27a^3+64= | | x^2+3x+88=0 | | x(x+3)=88ft^2 |